Development of interactive teaching and learning module (shearing stress in beams) - Rohit Prasad. (2011)
The project aims to develop an application that would enable a better learning experience for the subject Mechanics of Materials. This application would focus on the Shear Stress in Beams and would enable the students to better visualize the actual scenario with the help of animations and interactive platform. The software consists of two modules one being the learning module and other the teaching module. This feature allows the user to primarily gain knowledge of the concept with better visualization using the learning module and apply the understanding in the teaching module. The learning module with flash animation and interaction would enable to understand the shear stress acting on beams better. The teaching module would enhance the understanding and with the interactive features would keep the user engaged to perform various tasks. The learning module is capable of calculating Shear Force and Bending Moment diagrams for beams and also to calculate Shear stress in beams of different shapes. The solutions would serve as a guideline and ensure to verify the calculations attempted by the student. The software was developed primarily on Visual Basic platform with additional free and trial software for graphics and animations. The software remains simple and intuitive in usage, which can be downloaded and executed easily.